A multicentre, randomised controlled, non-inferiority trial, comparing nasal high flow with nasal continuous positive airway pressure as primary support for newborn infants with early respiratory distress born in Australian non-tertiary special care nurseries (the HUNTER trial): study protocol. Issue 6 (23rd June 2017) - Manley, Brett J; Roberts, Calum T; Arnolda, Gaston R B; Wright, Ian M R; Owen, Louise S; Dalziel, Kim M; Foster, Jann P; Davis, Peter G; Buckmaster, Adam G
Abstract : Introduction: Nasal high-flow (nHF) therapy is a popular mode of respiratory support for newborn infants. Evidence for nHF use is predominantly from neonatal intensive care units (NICUs). There are no randomised trials of nHF use in non-tertiary special care nurseries (SCNs). We hypothesise that nHF is non-inferior to nasal continuous positive airway pressure (CPAP) as primary support for newborn infants with respiratory distress, in the population cared for in non-tertiary SCNs. Methods and analysis: The HUNTER trial is an unblinded Australian multicentre, randomised, non-inferiority trial. Infants are eligible if born at a gestational age ≥31 weeks with birth weight ≥1200 g and admitted to a participating non-tertiary SCN, are <24 hours old at randomisation and require non-invasive respiratory support or supplemental oxygen for >1 hour. Infants are randomised to treatment with either nHF or CPAP. The primary outcome is treatment failure within 72 hours of randomisation, as determined by objective oxygenation, apnoea or blood gas criteria or by a clinical decision that urgent intubation and mechanical ventilation, or transfer to a tertiary NICU, is required. Secondary outcomes include incidence of pneumothorax requiring drainage, duration of respiratory support, supplemental oxygen and hospitalisation, costs associated with hospital care, cost-effectiveness, parental stress and satisfaction and nursing workload. Ethics and dissemination: Multisite ethical approval for the study has been granted by The Royal Children's Hospital, Melbourne, Australia (Trial Reference No. 34222), and by each participating site. The trial is currently recruiting in eight centres in Victoria and New South Wales, Australia, with one previous site no longer recruiting. The trial results will be published in a peer-reviewed journal and will be presented at national and international conferences. Trial registration number: Australian and New Zealand Clinical Trials Registry (ANZCTR): ACTRN12614001203640; pre-results.